Study of the work of modern logging machines in mountain conditions - Glushkov Sergey; Boyadzhiev Dmitryi; Chernykh Aleksander; Popikov Petr; Afonichev Dmitryi; Abramov Vitaliy; Polukarov Dmitryi; Savchenko Konstantin; Zhuzhukin Stanislav (BIO Web of Conferences)
The article presents the results of a study on the operation of the Mounty 4000 machine with the Woody H60 processor head in the mountainous conditions of Bulgaria. The structuring of the machine operation cycle was carried out and for each component the values of their durations were obtained in the course of a production experiment. This allows predicting the productivity of work, as well as the economic efficiency of using the “mountain harvester” in logging. In the course of the simulation experiment, the dependence of the damage of tree trunks left in the cutting area on the density of planting, the distance of skidding and the intensity of felling during the primary transportation of wood was established. This allows for a comprehensive assessment of the functioning of the Mounty 4000 machine simultaneously from economic and environmental points of view at the stage of technological design of logging operations.